Mukesh Shrestha's Paintings: Visual Narration of Buddhist Myths - Sharma, Yam Prasad (Journal of Fine Arts Campus, 2023)
In Mukesh Shrestha's compositions, Buddhist icons, images, symbols and figures have been reread and reformulated along with altered abstract background having sublime setting with magical and mystical atmosphere. Spontaneous visual rhythm is ever present in both foreground and background due to sinuous shapes and flowing colorful form. The archetypal characters and contents in coherent colors convey the message of coexistence, meditation and peace. The artist is in the quest of harmony and order in the state of chaos. Friendly and comfortable color combination sustains the viewers' interest. The artwork creates its own unique world with multiple significances to explore. The fineness of form adds intensity to visual experience. The primitive textures arouse the tactile sensation giving way to the imaginative flight to the far distance in time and space. The unique visual compositions present the aesthetic blend of tradition and modernity, myths and mysticism, the individual self and the cosmos. The condensed visual form presents the retrospection, recollection of native cultural treasure and anticipation of prosperity and peace. Fine craftsmanship and minutely detailed works with precision give a clue to the artist's patience and dedication. Monumental figures of divinity decked with traditional decorum along with symbols like lotus and vajra suggest invisible and intangible dimensions of the reality. Ritual postures and gestures convey a sense of mystical procession, a journey to the world beyond.